The problem of sociological and motivational analysis of consumption in the hyper-digital market - Barbeta Viñas, Marc (Política y Sociedad, 2026)
The objective of this work is to develop a critical reflection on the role played by the sociomotivational processes of consumption in the current hyper-digital market context. It problematizes how the market research model based on the use of algorithms and big data, which predominates on large platforms, would be replacing approaches characteristic of sociological analysis-especially those that address the why of consumption from the social and affective ties of consumers, that is, the sociomotivational perspective. It is argued that, instead, a research/promotion model is being constructed that, in practice, hinders sociomotivational development and makes its study impossible, as it becomes exclusively defined by an atheoretical, correlational, and predictive analysis, where what matters is the modification of reality and the attainment of profit, without this implying advances in the sociological understanding of consumer behavior. Finally, the work presents some initial theoretical and conceptual.